Patients Age 40 Years and Younger with Multiple Myeloma Have the Same Prognosis as Older Patients: An Analysis of Real-World Patients' Evidence from Latin America - Martinez-Cordero, H (2023)
PURPOSEMultiple myeloma (MM) is a highly heterogeneous, incurable disease most frequently diagnosed in the elderly. Therefore, data on clinical characteristics and outcomes in the very young population are scarce.PATIENTS AND METHODSWe analyzed clinical characteristics, response to treatment, and survival in 103 patients with newly diagnosed MM age 40 years or younger compared with 256 patients age 41-50 years and 957 patients age 51 years or older.RESULTSThere were no statistical differences in sex, isotype, International Scoring System, renal involvement, hypercalcemia, anemia, dialysis, bony lesions, extramedullary disease, and lactate dehydrogenase (LDH). The most used regimen in young patients was cyclophosphamide, bortezomib, dexamethasone, followed by cyclophosphamide, thalidomide, dexamethasone and bortezomib, thalidomide, dexamethasone. Of the patients age 40 years or younger, only 53% received autologous stem-cell transplant (ASCT) and 71.1% received maintenance. There were no differences in overall survival (OS) in the three patient cohorts. In the multivariate analysis, only high LDH, high cytogenetic risk, and ASCT were statistically associated with survival.CONCLUSIONIn conclusion, younger patients with MM in Latin America have similar clinical characteristics, responses, and OS compared with the elderly. © American Society of Clinical Oncology.